Transcendental presuppositions and ideas of reason - McLaughlin, Peter (Kant-Studien, 2014)
Abstract: In the Introduction to the Critique of Judgment Kant seems to present the “transcendental deduction” of the (subjective) purposiveness of nature whose necessity he had denied in the Appendix to the Critique of Pure Reason. The so-called First Introduction to the CJ promised two transcendental deductions of the (objective) purposiveness of nature, which the published text did not deliver. This paper analyzes the arguments of the CPR-Appendix showing that each of its two parts discusses a different sort of deduction. The fact that Kant at various times envisioned at least five very different deductions in the same context is taken as an occasion to rethink the project that Kant sketches in the Appendix to the CPR.
Gesehen am 01.12.2020